(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The reflex of scenography: XIX century heritage and contemporary perspectives) focuses on scenography since the 1980s, with a special interest in Italian theatre. It articulates an opening of the theoretical framework of scenography accounting for the transformation theatre has undergone since the second half of the Twentieth Century. In so doing, it shows some continuity with the past while also accounting for new tendencies in the construction of the performative space, which appear to be informed by a dialectics between the scene as sensorial stimulus and the scene as sign. This tension is engaged according to its present forms as a reflection of the artists’ contemporary sensibility towards life and society.